Diagnoza systemu kształcenia w kontekście wprowadzenia Krajowych Ram Kwalifikacji: Diagnosis of the education system in the context of the National Qualifications Framework - Sakowska, Aneta (Management and Administration Journal, 2021)
Education is a process. Continuous, divided into levels, infinite. Tertiary education level is an important element subjected to reorganization in past few years. The signing of the Bologna Declaration determined the changes in the education system at the high education level. Economic realities in Poland has changed as well as educational needs, candidates for study. Education must keep up with these innovations. Today‟s student is significantly different from a student 20 years ago. Therefore changes are necessary. National Qualifications Framework is an attempt to find a common language with education systems in Europe. The objective of the paper is to diagnose the system of education in the context of the National Qualifications Framework. Elaboration was based on a review of available literature of the subject, specialized and preliminary empirical research.